Synthesis and antimicrobial activity of new thiazole-2(3H)-thiones containing 1,1,3-trisubstituted cyclobutane - Ahmedzade, M; Kirilmis, C; Cukurovali, A; Dilsiz, N (Bureau Scientific Publ, 2003)
The reaction of potassium salts of RNHCSSK with 2-chloro-1-(3-methyl-3-phenylcyclobutyl)ethan-1-one in ethanol at 78-80degreesC afforded new 1,3-thiazole-2(3H)-thiones containing 1,1,3-trisubstituted cyclobutane rings at C-4. The antimicrobial activities of these compounds were also investigated against seven different microorganisms, and some of them were found to be active against several of the microorganisms at higher concentrations.
Keywords: alpha-haloketone; cyclobutane; dithiocarbamate; 1,3-thiazole-2(3H)-thiones; antimicrobial activity